Uji Aktivitas Antibakteri Ekstrak Kombinasi Umbi Bawang Tiwai dan Kulit Buah Lemon Terhadap Pertumbuhan Staphylococcus aureus dan Escherichia coli: Antibacterial Activity Test of Combination of Tiwai Onion Bulbs and Lemon Peel on the Growth of Staphylococcus aureus and Escherichia coli - Adinda Niti Meilaningrum; Novita Eka Kartab Putri; Yurika Sastyarina (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
Tiwai onion (Eleutherine americana (Aubl.) Merr) is a plant that contains several groups of secondary metabolites, one of which is the alkaloid group. Lemon rind (Citrus limon) is a plant that contains more than 2.5% essential oil and hesperidin. Several classes of secondary metabolite compounds from these two plants have antibacterial activity. This study aims to determine the characteristics of the extract and the antibacterial activity of the extract combination. The extract characteristics were tested in the form of organoleptic, pH and solubility. Meanwhile, the antibacterial activity test was carried out by using the well diffusion method. The results obtained were the characteristics of the tiwai bulb extract and lemon peel in the form of organoleptic (color: blackish red and yellow, thick texture, distinctive aroma of onion bulbs and lemon peel); pH (6.4 and 4.8); solubility (soluble in ethanol, methanol and aquades) and antibacterial activity at a concentration of 12: 3 with an average of 8.75mm (S. aureus) and 7mm (E.coli); 12: 6 with a mean of 11mm (S.aureus) and 7.25mm (E.coli); 12: 8 with an average of 12.25mm (S.aureus) and 13.75mm (E.coli). It can be concluded that at a concentration of 12: 8 the combination of these extracts had the highest average inhibition zone in inhibiting the two bacteria.